2013
DOI: 10.1186/1423-0127-20-86
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate-mediated cardioprotection by Akt/GSK-3β/caveolin signalling in H9c2 rat cardiomyoblasts

Abstract: BackgroundEpigallocatechin-3-gallate (EGCg) with its potent anti-oxidative capabilities is known for its beneficial effects ameliorating oxidative injury to cardiac cells. Although studies have provided convincing evidence to support the cardioprotective effects of EGCg, it remains unclear whether EGCg affect trans-membrane signalling in cardiac cells. Here, we have demonstrated the potential mechanism for cardioprotection of EGCg against H2O2-induced oxidative stress in H9c2 cardiomyoblasts.ResultsExposing H9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 49 publications
3
34
0
Order By: Relevance
“…Crucially, the CAV-1 expression level was markedly affected by the addition of H 2 O 2 to the culture medium; the CAV-1 level decreased by nearly 50-70%. Similarly, previous studies demonstrated that the expression of CAV-1 is significantly decreased after H 2 O 2 treatment in cardiomyocytes and skeletal muscle cells (26,27). Several studies have suggested that the rapid degradation of CAV-1 protein could be caused by the ubiquitin-proteasome pathway, particularly after oxidative injury (28,29).…”
Section: Discussionmentioning
confidence: 60%
“…Crucially, the CAV-1 expression level was markedly affected by the addition of H 2 O 2 to the culture medium; the CAV-1 level decreased by nearly 50-70%. Similarly, previous studies demonstrated that the expression of CAV-1 is significantly decreased after H 2 O 2 treatment in cardiomyocytes and skeletal muscle cells (26,27). Several studies have suggested that the rapid degradation of CAV-1 protein could be caused by the ubiquitin-proteasome pathway, particularly after oxidative injury (28,29).…”
Section: Discussionmentioning
confidence: 60%
“…Interestingly, proteomic studies demonstrated that EGCG has multiple cellular targets and binds to the 67kDa laminin receptor, caveolin-1 and -3, β-actin, myosin 9 and vimentin. Caveolin would serve as a membrane raft that may help mediate cardioprotective EGCG transmembrane signaling [61]. Moreover, in a high glucose model of arrhythmia in diabetic hearts, ECGC reverted the low levels of connexin 43 expression in a p38 MAPK-dependent manner in RNVC [62].…”
Section: Flavanolsmentioning
confidence: 98%
“…Hydrogen peroxide also alters the expression of adherens and gap junction proteins increasing intracellular ROS and Ca 2+ levels [61]. These effects were attenuated by pre-treatment with EGCG.…”
Section: Flavanolsmentioning
confidence: 98%
“…40 Akt/Gsk-3β pathway has been shown to be involved in modulating oxidative stress and apoptosis, and the activation of Akt/Gsk-3β pathway preserved heart function and alleviated MI/R injury. 49 In this study, we clarified that the Akt/Gsk-3β pathway was activated by catechin and this activation was mediated by MIAT down-regulation in H/R-induced H9C2 cells. 47,48 Importantly, the activation of Akt/Gsk-3β pathway is involved in the cardioprotection function of EGCG.…”
Section: Discussionmentioning
confidence: 80%
“…47,48 Importantly, the activation of Akt/Gsk-3β pathway is involved in the cardioprotection function of EGCG. 49 In this study, we clarified that the Akt/Gsk-3β pathway was activated by catechin and this activation was mediated by MIAT down-regulation in H/R-induced H9C2 cells. To the best of our knowledge, no other studies figured out catechin improved mitochondrial function and reduced the apoptosis of H/R-induced H9C2 cells through regulating lncRNA MIAT/Akt/Gsk-3β pathway, which revealed the underlying mechanism of catechin in protecting against H/R-induced myocardial cell apoptosis.…”
Section: Discussionmentioning
confidence: 80%